Implementation of Notary House Employment Agreements in the Selling of Land and Building - Indra Muliawan; Jawade Hafidz (Sultan Agung Notary Law Review, 2021)
The research entitled "Implementation of Notary House Vacationing Agreements in the Sale and Purchase of Land and Buildings in Randudongkal Pemalang Regency", in order to find out and analyze the legal protection of buyers in the implementation of notarial house emptying agreements in the sale and purchase of land and buildings, as well as obstacles and solutions to realize a sense of belonging justice for the implementation of the notarial vacancy agreement in the sale and purchase of land and buildings. This study uses an empirical juridical approach, which is a legal research conducted by researching and examining existing facts in line with observations in the field. Legal protection against the buyer in the implementation of the notarial house emptying agreement in the sale and purchase of land and buildings, is considered This is important because the sale and purchase agreement has been signed so that the object of sale and purchase has turned into the property of the buyer, however the seller or other person who occupies the house has not been able to leave or vacate the house. The seller or other person who occupies the house cannot immediately vacate the house after the rights have been transferred, because they are not ready to move house or have not obtained a replacement house. Based on these circumstances, the parties agree to make a separate agreement to complete the sale and purchase agreement that has been made. The agreement is agreed upon by the seller and the buyer or the parties in the form of an agreement to vacate the house which is notarized. Legal certainty of a notarial vacancy agreement, concerning when the seller or other person who occupies the house leaves or vacates the house. If the specified date turns out to be that the seller or other person occupying the house cannot leave or vacate the house, a fine per day is imposed, the amount of which is agreed upon in the agreement by the seller and buyer or the parties. In the notarial agreement to vacate the house, it is necessary to include a clause that the buyer is obliged to provide severance pay to the seller as much as agreed by both parties. Severance pay must be paid by the buyer to the seller after the house is delivered empty by the seller to the buyer. This is intended as compensation that has been agreed between the seller and the buyer, and as a balance between the rights and obligations obtained by both parties in the agreement. If the seller or other person occupying the house is ready to leave or vacate the house, but the buyer is unable to pay or provide severance pay to the seller or other person who occupies the house, the buyer is subject to a fine as much as agreed by the parties.